Highly enantioenriched 2-azabenzonorbornenes from 7-azabenzonorbornadienes by asymmetric hydroboration-oxidation and tandem deoxygenation-rearrangement-electrophile trapping - Hodgson, D; Winning, L (2006)
3-exo-Substituted 2-azabenzonorbornenes are accessible from 7-azabenzonorbornadienes in good yields and high enantiomeric excess via asymmetric hydroboration-oxidation, followed by tandem deoxygenation- rearrangement-electrophile trapping and also provide access to substituted aminomethylindenes. © Georg Thieme Verlag Stuttgart.